The Analysis Study of Risk of Complication Post Tonsillectomy in Children : A Comprehensive Systematic Review - Sasanti, Ratri Ridha; Nandawati , Itsnaini Maulidya (The International Journal of Medical Science and Health Research, 2024)
Background: This study aims to provide a comprehensive regarding possible postoperative complications following tonsillectomy in children, highlighting how various interventions and preoperative measures can influence outcomes and postoperative recovery. Methods: Following PRISMA 2020 guidelines, this systematic review focused exclusively on full-text articles published in English between 2014 and 2024. Result: The study conducted a comprehensive review of over 100 publications sourced from reputable databases, including ScienceDirect, SagePub, and PubMed. Following an initial screening, eight publications were identified as warranting more in-depth analysis. Consequently, a thorough review of these selected studies was performed to ensure a detailed and rigorous evaluation. Conclusion: The tonsillar lodge is crucial for children's health, but postoperative complications can arise in various forms. Despite advancements in anesthesia, challenges remain due to the surgical environment. Infectious and traumatic complications are prevalent, requiring timely detection and intervention. Timely detection and intervention are essential to optimizing patient outcomes and addressing these potential issues effectively.